Key research themes on travel behavior, lifestyle, and sustainable urban mobility. Issue 1 (2nd January 2016) - Van Acker, Veronique; Goodwin, Phil; Witlox, Frank
Abstract: The concept of lifestyle adds a behavioral component to travel models that used to be dominated by engineering and econometric traditions. This article presents an overview of how lifestyle is defined and measured in transport studies, and how travel behavior is influenced by lifestyles. Lifestyles are often used pragmatically rather than theoretically in the behavior studies. Nevertheless, some important theoretical contributions have been made, especially in sociology by scholars such as Weber, Bourdieu, Ganzeboom, and Schulze who agree on the communicative character of lifestyles: individuals express their social position through specific patterns of behavior, consumption, and leisure. These behavioral patterns are shaped by underlying opinions and orientations, including beliefs, interests, and attitudes. Thus, travel behavior is not simply determined by price, speed, and comfort but is also related to attitudes, status, and preferences. Because lifestyle has many different dimensions, a variety of measurement approaches exists. Nevertheless, most studies suggest that travel behavior is conditioned by specific lifestyles. How lifestyles themselves can be modified to promote more sustainable patterns of transport has not received much attention to date. This article argues that lifestyles need to be considered as dynamic rather than as static and given, and that future research could delve more deeply into this area.